Co-administration of a plasmid DNA encoding IL-15 improves long-term protection of a genetic vaccine against Trypanosoma cruzi. - Christopher S Eickhoff; Jose R Vasconcelos; Nicole L Sullivan; Azra Blazevic; Oscar Bruna-Romero; Mauricio M Rodrigues; Daniel F Hoft (Public Library of Science (PLoS), 2011)
Immunization of mice with the Trypanosoma cruzi trans-sialidase (TS) gene using plasmid DNA, adenoviral vector, and CpG-adjuvanted protein delivery has proven highly immunogenic and provides protection against acute lethal challenge. However, long-term protection induced by TS DNA vaccines has not been reported. The goal of the present work was to test whether the co-administration of a plasmid encoding IL-15 (pIL-15) could improve the duration of protection achieved through genetic vaccination with plasmid encoding TS (pTS) alone.We immunized BALB/c mice with pTS in the presence or absence of pIL-15 and studied immune responses [with TS-specific IFN-γ ELISPOT, serum IgG ELISAs, intracellular cytokine staining (IFN-γ, TNF-α, and IL-2), tetramer staining, and CFSE dilution assays] and protection against lethal systemic challenge at 1 to 6 months post vaccination. Mice receiving pTS alone developed robust TS-specific IFN-γ responses and survived a lethal challenge given within the first 3 months following immunization. The addition of pIL-15 to pTS vaccination did not significantly alter T cell responses or protection during this early post-vaccination period. However, mice vaccinated with both pTS and pIL-15 challenged 6 months post-vaccination were significantly more protected against lethal T. cruzi challenges than mice vaccinated with pTS alone (P<0.05). Improved protection correlated with significantly higher numbers of TS-specific IFN-γ producing total and CD8(+) T cells detected>6 months post immunization. Also, these TS-specific T cells were better able to expand after in vitro re-stimulation.Addition of pIL-15 during genetic vaccination greatly improved long-term T cell survival, memory T cell expansion, and long-term protection against the important human parasite, T. cruzi.